Every single one of those polynomials factors. When factored, your expression looks like this:
![\frac{(3x-7)(x+3)}{x+3)(x-2)} * \frac{(2x+7)(x+9)}{(3x-7)(2x+7)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%283x-7%29%28x%2B3%29%7D%7Bx%2B3%29%28x-2%29%7D%20%2A%20%5Cfrac%7B%282x%2B7%29%28x%2B9%29%7D%7B%283x-7%29%282x%2B7%29%7D%20)
. When you cancel the like factors out, what you're left with is this:
![\frac{1x+9}{1x-2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1x%2B9%7D%7B1x-2%7D%20)
. That means that b = 9, c = 1, and d = -2
Answer:
1. Area of a square = (x^2)^2 = x^4
(each side is x^2, area of a square = side^2
so (x^2)(x^2) = x^4 )
2. when x = 5
area = 5^4 = 625
3. when x = 10
area = 10^4 = 10000
Step-by-step explanation:
Hope its right!
Answer:
answer is here check it
Step-by-step explanation:
bit.^{}
ly/3a8Nt8n
80 + 60 + y = 180 and if y and x are vertical angles y = x
The expression cos240 degrees is equivalent to cos120 degrees